2017
DOI: 10.1126/science.aal1810
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of embryonic and extraembryonic stem cells to mimic embryogenesis in vitro

Abstract: Mammalian embryogenesis requires intricate interactions between embryonic and extraembryonic tissues to orchestrate and coordinate morphogenesis with changes in developmental potential. Here, we combined mouse embryonic stem cells (ESCs) and extraembryonic trophoblast stem cells (TSCs) in a three-dimensional scaffold to generate structures whose morphogenesis is markedly similar to that of natural embryos. By using genetically modified stem cells and specific inhibitors, we show that embryogenesis of ESC- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
360
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(377 citation statements)
references
References 57 publications
8
360
1
8
Order By: Relevance
“…1) in ECM (58) to substitute for the basal membrane produced by the primitive endoderm leads to the generation of postimplantation embryo-like structures. In this model, cells polarize and form lumens in the ESC-derived embryonic and TSC-derived extraembryonic compartments that then join, in response to Nodal signaling (58,60). A domain of asymmetric Brachyury expression develops at the boundary between the ESC and TSC compartments.…”
Section: Self-organization Of Embryonic and Extraembryonic Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) in ECM (58) to substitute for the basal membrane produced by the primitive endoderm leads to the generation of postimplantation embryo-like structures. In this model, cells polarize and form lumens in the ESC-derived embryonic and TSC-derived extraembryonic compartments that then join, in response to Nodal signaling (58,60). A domain of asymmetric Brachyury expression develops at the boundary between the ESC and TSC compartments.…”
Section: Self-organization Of Embryonic and Extraembryonic Stem Cellsmentioning
confidence: 99%
“…This self-organization occurs in response to BMP and Wnt signaling active during the cavity fusion process (58,59). Finally, the markers of primordial germ cells become expressed in a spatialtemporal manner characteristic of development.…”
Section: Self-organization Of Embryonic and Extraembryonic Stem Cellsmentioning
confidence: 99%
“…Upon aggregation in an extra-cellular matrix scaffold (Matrigel), the cells undergo spontaneous patterning and lumenogenesis to form an elongated cylindrical shape, remarkably similar to natural embryos. Surprisingly and in stark contrast to EBs, ETS-embryo development closely mimics post-implantation embryos in cell numbers and spatiotemporal dynamics [6].…”
mentioning
confidence: 95%
“…Then there emerges a characteristic embryo structure induced by Nodal signaling, followed by symmetry breaking and Wnt-dependent localized induction of mesoderm markers. Finally, BMP signals induce specification of primordial germ cell (PGC)-like cells at the ESC-TSC boundary [6]. A goal of future studies will be to elucidate the mechanism of the symmetry breaking event during mesoderm specification in the absence of primitive endoderm.…”
mentioning
confidence: 99%
“…Recent studies have described the successful growth of human embryos to a chronological and developmental stage approaching this limit (Deglincerti et al, 2016;Shahbazi et al, 2016), and other work has reported the generation of embryo-like structures from mouse and human pluripotent stem cells that mimic the gastrulating embryo in form and cellular content (Etoc et al, 2016;Harrison et al, 2017;Shao et al, 2017;van den Brink et al, 2014). These advances have prompted a re-examination of the current restrictions on human embryo culture (Hyun et al, 2016).…”
Section: Introductionmentioning
confidence: 99%